The Frequency of Kell Red Cell Antigens (K,k) Among The Major Sudanese Tribes - Akasha, Ahmed Siddig (Recent Research in Science and Technology, 2012)
Objective: to determine the frequency of Kell-1 and Kell-2 and their gene frequencies in the Sudanese population. Design: This study was carried out on 500 samples in five major Sudanese tribes. Each sample was tested for Kell-1 and Kell-2 by indirect coombs’ test using anti Kell-1 and Kell-2 antisera. Setting: AL-Neelain University – College of Medical Laboratory Sciences – Sudan – Khartoum. Results: The frequency of Kell-1among the tribes was found to be 5.6% while that of Kell-2 was found to be 99.6%. Gene frequencies of Kell-1 and Kell-2 were found to be 0.03 and 0.97 respectively. Conclusions: The frequency of Kell-1 is 5.6% and its gene frequency is 0.03 while the positivity of Kell-2 is 99.6% and its gene frequency is 0.97.